EXPERIMENTAL STUDIES OF ELEMENTS OF METAL CYLINDRICAL STRUCTURES STRENGTHENED BY EXTERNAL TRANSVERSAL CFRP REINFORCEMENT (Collection of scientific works «Modern structures of metal and wood», 2022)
One  of  the  modern  ways  to  increase  the  bearing  capacity  of  the  walls  of  metal cylindrical structures that perceive the action of internal pressure is the external transversely directed reinforcement by  fiber  reinforced plastics  (FRP),  the  most  effective  type  of  which  is  made  from carbon fibers (CFRP). Consideration of metal cylindrical shells, which perceive the action of internal pressure and are reinforced with external transversely directed FRP reinforcement, makes it possible to obtain the values of the stress state parameters of the corresponding structures. At the same time, analytical methods for estimating these parameters do not have the necessary experimental justification. In  this  connection,  experimental  studies  of  the  stress  state  of  elements  of  models  of  metal cylindrical structures externally reinforced with transversely directed FRP based on high strength and high  modulus  carbon  fibers  were  carried  out.  The  results  of  tests,  including  taking  into  account variable operating temperatures, are presented in this paper in comparison with the conclusions of the previously proposed practical methods of the corresponding analytical assessment. The  paper  substantiates  the  applicability  of  applied  analytical  methods  for  determining  the parameters of the stress state in the elastic stage of deformation of the elements of the complex walls of metal cylindrical shells externally reinforced with transversely directed FRP elements made on the basis of normal modulus and high modulus carbon fibers.